Rancang Bangun Sistem Website Jago-Investasi Sebagai Pembelajaran Berinvestasi Mahasiswa Uhamka (Fakultas Ekonomi Dan Bisnis) - Rifqi Favian Hibatullah; Ahmad Rizal Dzikrillah; Pandu Fahrizal; Dafa Setyo Nugroho (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2024)
By studying investment, it will make a significant impact on future economic development, both or individually. Even so, there are not a few students who are less fond of and active in studying investment because of system that making students easily distorted by other content. With advances technology, using website as learning media is a powerfull way to attract students to study investment materials. “Jago-Investasi” website aims to develop investment skills, especially for stundents of Faculty of Business and Economy Universitas Muhammadiyah Prof. Dr. HAMKA (UHAMKA), so that students can easily take advantage of this website as learning material that focuses on investment without distortion while studying materials. The Design method used in this design is waterfall, there are four stages required, namely Requirements Analysis, System Design, Implementation and Testing. With the